(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The proposed research Provides an approach for hiding an encrypted text in side a digital image. Where the text is encrypted in a complex manner used method of PlayFair to encrypt clear text and to increase security put lettering ciphertext on the geometric shape clockwise and then we write the ciphertext output in the form of lines, taken new ciphertext and converted to Ascii code and then to binary and hidden text in bits least importance in the picture. The results were good by PNSR scale